The Joke – a(n) (Un)Important Form of Humor - Vesna Trifunović (University of Belgrade, 2016)
The joke is a form of humor that has not received as much attention by Serbian folkloristics and anthropology as it deserves. A possible reason for this is that the joke is so thoroughly incorporated into everyday communication that it tends to be overlooked. Furthermore, the joke as a form of humor has not even been adequately recognized, witness the lack of an adequate definition and the fact that it is frequently confused with similiar forms of folklore, such as the (vic). This paper examines the form, use and meaning of the joke in Serbian society today, and then proceeds to offer a distinct definition of the joke, at the same time specifying the distinctions between the joke and similar forms of humor. Finally, it addresses the question of the place that the joke should be assigned in folklore material, and also its significance in anthropological and folkloristic research.